2016
DOI: 10.1007/s00018-016-2359-y
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Kv7 channels and excitability in the brain

Abstract: Neuronal Kv7 channels underlie a voltage-gated non-inactivating potassium current known as the M-current. Due to its particular characteristics, Kv7 channels show pronounced control over the excitability of neurons. We will discuss various factors that have been shown to drastically alter the activity of this channel such as protein and phospholipid interactions, phosphorylation, calcium, and numerous neurotransmitters. Kv7 channels locate to key areas for the control of action potential initiation and propaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
144
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(158 citation statements)
references
References 170 publications
(249 reference statements)
4
144
0
2
Order By: Relevance
“…We searched previously published datasets of largescale sequencing studies on the causes of neurodevelopmental disability for other reports of de novo KCNQ5 mutations and found c.867G>T (p.Lys289Asn), c.1328G>A (p.Arg443Gln), and c.1727A>G (p.His576Arg) in the supplemental data from 820 probands in Lelieveld et al 17 However, these variants were not identified as candidate causes of neurodevelopmental disability in the course of the authors' statistical analyses. The largest currently published cohort of individuals with developmental disorders (the Deciphering Developmental Disorders study, n ¼ 4,293) did not feature any KCNQ5 de novo variants, 18 nor were any included in the data from the cohort of 2,508 autism probands from Iossifov et al 19 Because of the above evidence associating KCNQ5 mutations with neurodevelopmental disorders, as well as prior evidence that mutations in KCNQ2 (encoding Kv7.2) and KCNQ3 (encoding Kv7.3) most likely cause neurological disease via reduced basal M-current (and subsequent neuronal hyperexcitability), 20 the impact of each mutation was characterized in vitro. Figure 2 shows that heterologous expression of homomeric WT Kv7.5 channels yielded voltage-dependent K þ currents that activated slowly upon depolarization with a V 1/2 of activation of À46.2 5 1.8 mV (n ¼ 7), as has been described previously.…”
Section: Resultsmentioning
confidence: 99%
“…We searched previously published datasets of largescale sequencing studies on the causes of neurodevelopmental disability for other reports of de novo KCNQ5 mutations and found c.867G>T (p.Lys289Asn), c.1328G>A (p.Arg443Gln), and c.1727A>G (p.His576Arg) in the supplemental data from 820 probands in Lelieveld et al 17 However, these variants were not identified as candidate causes of neurodevelopmental disability in the course of the authors' statistical analyses. The largest currently published cohort of individuals with developmental disorders (the Deciphering Developmental Disorders study, n ¼ 4,293) did not feature any KCNQ5 de novo variants, 18 nor were any included in the data from the cohort of 2,508 autism probands from Iossifov et al 19 Because of the above evidence associating KCNQ5 mutations with neurodevelopmental disorders, as well as prior evidence that mutations in KCNQ2 (encoding Kv7.2) and KCNQ3 (encoding Kv7.3) most likely cause neurological disease via reduced basal M-current (and subsequent neuronal hyperexcitability), 20 the impact of each mutation was characterized in vitro. Figure 2 shows that heterologous expression of homomeric WT Kv7.5 channels yielded voltage-dependent K þ currents that activated slowly upon depolarization with a V 1/2 of activation of À46.2 5 1.8 mV (n ¼ 7), as has been described previously.…”
Section: Resultsmentioning
confidence: 99%
“…Impairment in Na v channel expression results in delayed maturation of the nodes of Ranvier and slows down nerve conduction velocity (39,40), whereas mutations in nodal potassium channels are associated with myokymia, epilepsies, and encephalopathies (41,42). The mechanisms leading to the accumulation of Na v channels at the nodes in the PNS are dependent on neurofascin-186 and NrCAM (15).…”
Section: Discussionmentioning
confidence: 99%
“…Kv7.2 and Kv7.3 heterotetramers (encoded by the KCNQ2 and KCNQ3 genes, respectively) are the main component of the neuronal M-current, a non-inactivating voltage dependent potassium current which controls neuronal excitability and firing frequency [1,2]. Consequently, mutations in these genes underlie genetic excitatory neuropathological conditions such as epilepsy or encephalopathy [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the genes encoding human Kv7.2 give rise to benign familial neonatal epilepsy (BFNE), a dominantly inherited idiopathic epilepsy [1]. It was initially proposed that the reduction in current amplitude is the primary defect leading to disease, with a mere a 25–50% decrease of the M-current being sufficient for pathology [1921].…”
Section: Introductionmentioning
confidence: 99%